PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH OLEH MAJLIS AMANAH RAKYAT MALAYSIA: STRATEGI DAN IMPLEMENTASI - castrawijaya, cecepcastrawijaya; Bin Abu Bakar , Mohammad Hazwan (JURNAL MANAJEMEN DAKWAH, 2023)
The potential of MFIs in their development in a global world contributes up to 80% of the economic turnover of the middle-class that. In addition, the success of MFI development is largely determined by the role of multiple actors. The last fact is that there is an institution that is quite successful in managing MFIs, namely the Majlis Amanah Rakyat (MARA). Therefore, this study contains an analysis of the strategy used by MARA in starting businesses in the culinary field around Bintulu, Sarawak, Malaysia. The purpose of this study is to reveal how the strategy used by MARA in empowering businesses in the culinary field around Bintulu Sarawak Malaysia. This research is a qualitative descriptive study. The data collection technique used interviews by recording the results of the interviews as they were. The results of the study show that the MARA Strategy in encouraging the creation of self-sufficiency in Micro, Small, and Medium Enterprises (MSMEs) is divided into three, namely capacity building, capital procurement, and provision of supporting facilities. on the first strategy namely program training, consulting services, training and teaching in the field as well as special programs. The second strategy is to provide capital. Especially for people who meet the requirements and register for the program, they will receive capital assistance according to the provisions made by the MARA team. The last strategy is to provide supporting facilities. There are three types of facilities that will be obtained by MSMEs if they participate in this program, namely: shophouses, small shop, and the last is a kind of tent or street vendor for selling.